An exploratory study of student perceptions of the college environment at four selected colleges - Gatan, Fernando C. (1971)
This exploratory study analyzed the perceptions of college students in four colleges. Using self perceptions of students and their perceptions of their college environment, this study further probed into how the degree of consonance reported related to the self-reports of satisfaction along certain variables. The Transactional Analysis of Personality and Environment (TAPE) Form B was used to collect data which served as the basis for statistical measures on the concepts: self, college, faculty, administration and satisfaction. As a whole, the sample viewed the self and the college environment in a homogenized manner.